2015
DOI: 10.1166/jnn.2015.9745
|View full text |Cite
|
Sign up to set email alerts
|

Development of Composite Poly(Lactide-<I>co</I>-Glycolide)-Nanodiamond Scaffolds for Bone Cell Growth

Abstract: There are relatively few nanotechnologies that can produce nanocomposite scaffolds for cell growth. Electrospinning has emerged as the foremost method of producing nanofibrous biomimetic scaffolds for tissue engineering applications. In this study diamond nanoparticles were integrated into a polymer solution to develop a nanocomposite scaffold containing poly(lactide-co-glycolide) (PLGA) loaded with diamond nanoparticles. To investigate the effect of adding diamond nanoparticles to PLGA scaffolds, primary huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…The major drawback of CNTs is the presence of impurities of carbonaceous particles such as nanocrystalline graphite, amorphous carbon, fullerenes, and different metals (typically Fe, Co, Mo or Ni) used as catalysts during the synthesis phase, and also concerns with toxicity as they are resistant to degradation in vivo [51, 57]. More recently, other forms of carbonaceous nanoparticles such as graphene and nanodiamonds are also being investigated [58, 59]. …”
Section: Influence Of the Biophysical Microenvironment On Stem Cell Rmentioning
confidence: 99%
“…The major drawback of CNTs is the presence of impurities of carbonaceous particles such as nanocrystalline graphite, amorphous carbon, fullerenes, and different metals (typically Fe, Co, Mo or Ni) used as catalysts during the synthesis phase, and also concerns with toxicity as they are resistant to degradation in vivo [51, 57]. More recently, other forms of carbonaceous nanoparticles such as graphene and nanodiamonds are also being investigated [58, 59]. …”
Section: Influence Of the Biophysical Microenvironment On Stem Cell Rmentioning
confidence: 99%
“…Our PLGA-nanodiamond nanofibrous scaffolds supported the adhesion and growth of human osteoblast-like MG 63 cells to a similar degree as the pure PLGA nanofibrous scaffolds [68] but accelerated the growth of human bone marrow mesenchymal stem cells [61] (Figure 8). However, when nanodiamond nanoparticles were incorporated into PLA nanofibrous scaffolds, they had rather negative effects on human osteoblast-like MG 63 and Saos-2 cells.…”
Section: Nanofibers In Bone Tissue Engineeringmentioning
confidence: 72%
“…Nanofibrous scaffolds can be associated with another advanced technique in recent tissue engineering-controlled delivery of various types of stem cells, such as bone marrow mesenchymal stem cells [51,[61][62][63], adipose tissue-derived stem cells [64,65], neural tissue-derived stem cells [57], and induced pluripotent stem cells [20,34], and their appropriate differentiation into desired cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Brady et al . showed that electrospun PLGA nanocomposite bone scaffolds could be reinforced by the addition of DNDs [158]. PLGA nanocomposites with 2.3 wt% DNDs exhibited a two-fold increase in both elastic modulus and hardness.…”
Section: Tissue Engineeringmentioning
confidence: 99%